Aripiprazole Lauroxil: Development and Evidence-Based Review of a Long-Acting Injectable Atypical Antipsychotic for the Treatment of Schizophrenia - Citrome L; Correll CU; Cutler AJ; Dunbar M; Hoberg AR; Hopkinson C; Mattingly GW; McGrory JA; Rege B; Weiden PJ; McDonnell D (Neuropsychiatric Disease and Treatment)
Leslie Citrome,1 Christoph U Correll,2– 6 Andrew J Cutler,7,8 Martin Dunbar,9 Amber R Hoberg,10 Craig Hopkinson,9 Gregory W Mattingly,11,12 James A McGrory,9 Bhaskar Rege,9 Peter J Weiden,13 David McDonnell14 1New York Medical College, Valhalla, NY, USA; 2Department of Psychiatry, The Zucker Hillside Hospital, Northwell Health, Glen Oaks, NY, USA; 3Department of Psychiatry and Molecular Medicine, Donald and Barbara Zucker School of Medicine at Hofstra/Northwell, Hempstead, NY, USA; 4Center for Psychiatric Neuroscience, The Feinstein Institute for Medical Research, Northwell Health, New Hyde Park, NY, USA; 5Department of Child and Adolescent Psychiatry, Charité Universitätsmedizin Berlin, Berlin, Germany; 6German Center for Mental Health (DZPG), Partner Site Berlin, Berlin, Germany; 7Department of Psychiatry, SUNY Upstate Medical University, Syracuse, NY, USA; 8Neuroscience Education Institute, Lakewood Ranch, FL, USA; 9Alkermes, Inc, Waltham, MA, USA; 10WellMed Medical Management, South Texas Medical Center, San Antonio, TX, USA; 11Washington University School of Medicine, St. Louis, MO, USA; 12Midwest Research Group, St. Louis, MO, USA; 13Renaissance School of Medicine at Stony Brook University, Stony Brook, NY, USA; 14Alkermes Pharma Ireland Ltd, Dublin, IrelandAbstract: This review article describes why and how aripiprazole was formulated as aripiprazole lauroxil (AL), an extended-release antipsychotic agent that is delivered via a long-acting injectable formulation, and the clinical trials investigating its use. AL was formulated as an inactive prodrug of aripiprazole using LinkeRx® technology to provide a prolonged-release antipsychotic with predictable dissolution over time. The resulting AL pharmacokinetic profile is characterized by a long half-life and little peak-to-trough aripiprazole concentration variability across dosing intervals of every 1 month, every 6 weeks, and every 2 months. The prodrug technology was further refined to develop an AL initiation formulation with a somewhat faster release of aripiprazole, eliminating the need for a 21-day oral aripiprazole supplementation period. With this initiation formulation, AL treatment can be started in 1 day. Key AL characteristics, including pharmacokinetic profile and efficacy, safety, and tolerability data, are presented. In addition to the efficacy and safety established in clinical trials of oral aripiprazole, a placebo-controlled 12-week pivotal study investigated AL 441 mg and 882 mg monthly regimens in patients with acutely exacerbated schizophrenia and provided efficacy and safety information that led to US Food and Drug Administration approval in 2015. Thereafter, studies established the long-term safety profile and durability of the AL treatment effect. The 25-week, active-controlled ALPINE study evaluated the feasibility and effectiveness of AL 1064 mg every 2 months, initiated using the 1-day AL initiation regimen, without further oral supplementation beyond day 1, in patients hospitalized for acutely exacerbated schizophrenia with subsequent transition to outpatient care. In short-term and long-term studies, AL was generally well tolerated at initiation and during acute and maintenance treatment. Pharmacokinetic, efficacy, and safety characteristics support the use of AL across inpatient and outpatient treatment settings.Plain Language Summary: Treatment of schizophrenia with continuous antipsychotic medication has been shown to improve symptoms, daily functioning, and quality of life. One important option for antipsychotic treatment is a long-acting injectable medication. Antipsychotic injections can be administered weeks or months apart in place of daily oral medication. Aripiprazole lauroxil is a long-acting injectable antipsychotic for adults with schizophrenia that has several important features; it provides continuous, stable medication after monthly, every-6-week, or every-2-month injections, and multiple dose options are available (see video abstract). In addition, patients can start treatment with aripiprazole lauroxil using either a 1-day or 21-day initiation regimen with their first dose. The 1-day initiation regimen allows people with schizophrenia to start treatment during a doctor’s office visit or during a brief stay in the hospital. In short-term studies, aripiprazole lauroxil significantly reduced symptoms of acute schizophrenia. In longer-term studies, side effects were similar to those expected when using oral aripiprazole, and symptoms improved over extended durations of treatment lasting up to 3.5 years. Aripiprazole lauroxil’s safety and efficacy profile and multiple dosing and initiation options make it a treatment option for schizophrenia in inpatient and outpatient settings.Keywords: dosing, pharmacokinetics, phase 3 clinical trials, safety, treatment efficacy, treatment initiation